Nosocomial Sepsis and its Risk Factors: A Cross-Sectional Study in a Neonatal Intensive Care Unit - Yadav, Sunil Kumar; Yadav, SP; Kanodia, P; Bhatta, N K; Singh, R R; Khanal, B (Journal of BP Koirala Institute of Health Sciences, 2019)
Introduction: Nosocomial sepsis is a common and serious infection of neonates who are admitted in intensive care unit. They lead to significant morbidity and mortality in both developed and resource limited countries. The neonatal intensive care unit (NICU) is a suitable environment for disseminating the infections and, hence, needs preventive intervention. The study was carried out to determine the risk factors for nosocomial sepsis in neonatal intensive care unit. Material and Methods: This was a cross-sectional study conducted in a seven bedded teaching and referral hospital NICU. All neonates in NICU who did not have any sign of infection at admission and remained hospitalized for at least 48 hours were observed. Nosocomial sepsis was diagnosed according to the CDC criteria. Risk factors for nosocomial sepsis were analyzed with Chi-square test and Logistic regression model. P-value of <0.05 was considered significant. Results: Low birth weight (both preterm and IUGR) and mechanical ventilation were found to be related with nosocomial sepsis. Conclusions: Low birth weight and mechanical ventilation were the most important risk factors fornosocomial sepsis.